Concentration-Dependent Acute Toxicity of Parboiled Rice Mill Effluent in Labeo rohita: A Fish Bioassay Approach (International Journal of Scientific Research in Science and Technology, 2026)
Parboiled rice mill effluents (PRME) are among the most polluting agro-industrial wastewaters due to their exceptionally high organic load, nutrients, and suspended solids (Nanda et al., 2021; Das et al., 2023; Pandey & Chandra, 2024). The present investigation evaluates the acute toxicity of PRME at different concentrations on the freshwater fish Labeo rohita over a 96-h exposure period. Physico-chemical analysis of raw effluent revealed acidic pH, critically low dissolved oxygen, and extremely elevated BOD, COD, nutrients, alkalinity, and hardness, which are known to induce severe stress in aquatic organisms (Yadav et al., 2022; Singh & Srivastava, 2023). Acute toxicity bioassays were conducted using graded effluent concentrations (10%, 20%, 40%, 60%, 80%, and 100%). Mortality, behavioral abnormalities, and stress responses were recorded at 24-h intervals. Results demonstrated a clear concentration- and time-dependent increase in mortality, with severe behavioral disruptions at higher concentrations, consistent with previous fish bioassay studies (Kumar & Rai, 2021; Saha et al., 2023). The study confirms that untreated PRME poses serious ecological risks to freshwater fish and emphasizes the urgent need for effective treatment prior to discharge.